Identification and characterisation of Arabidopsis ER accessory proteins - Ferguson, Alison (2012)
ER accessory proteins are a novel class of endoplasmic reticulum (ER) proteins that facilitate the exit of polytopic membrane proteins from the ER. They are important for the correct targeting of their cognate polytopic membrane proteins to the plasma membrane (PM) and their absence leads to abnormal accumulation of their target in the ER. Until recently, it was not clear if such proteins exist in plants. However, work by Dharmasiri et al (2006) and Gonzales et al (2005) suggest that such proteins exists in plants too. Polytopic membrane proteins such as nutrient transporters, hormone transporters and sugar transporters are a very important class of proteins as they regulate many important physiological and biochemical processes. Better understanding of the targeting of these proteins to the PM is of considerable agronomic interest due to the importance of efficient use of resources in sustainable agriculture.